PELAKSANAAN PERATURAN MENTERI KESEHATAN NOMOR 1871/MENKES/PER/IX/2011 TENTANG PENCABUTAN PERATURAN MENTERI KESEHATAN NOMOR 339/MENKES/PER/V/1989 TENTANG PEKERJAAN TUKANG GIGI - Ni Wayan Adiani; I Gusti Ngurah Wairocana (Kertha Negara : Journal Ilmu Hukum, 2013)
The article is entitled "Ministry of Health Regulation Number1871/MENKESs/PER/IX/2011 regarding the Revocation of Ministry of HealthRegulation Number 339/MENKES/PER/V/1989 regarding Dental Handyman". Thisarticle utilizes normative analysis method combined with legislative approach andfactual approach. Needs of dental healthcare had been consequently increasing alongwith the increasing demand of the related healthcare services itself. One of thecontributing dental health care agents in society shall be the Dental Handyman. Itsexistence due to the enactment of Ministry of Health Regulation Number No.1871/MENKES/PER/IX/2011 remain a controversy. The regulation basically explainsthat after the disclosure or after certain dental handyman license expires, they shall nolonger be able to operate. Formulation of the problem shall be observed is theimplementation of Ministry of Health Regulation Number 1871/2011 along with itscorrelating factors. The results and conclusions obtained namely that Permenkes No.1871/MENKES/PER/IX/2011 is not yet implemented due to several factors, among other factors shall be the law, the law enforcing factor, availability of facility or means,society factors and cultural factors.